Ligand-specific conformational change drives interdomain allostery in Pin1 - Born, Alexandra; Soetbeer, Janne; Henen, Morkos A.; Breitgoff, Frauke; Polyhach, Yevhen; Jeschke, Gunnar; Vögeli, Beat (Nature communications, 2022)
Pin1 is a two-domain cell regulator that isomerizes peptidyl-prolines. The catalytic domain (PPIase) and the other ligand-binding domain (WW) sample extended and compact conformations. Ligand binding changes the equilibrium of the interdomain conformations, but the conformational changes that lead to the altered domain sampling were unknown. Prior evidence has supported an interdomain allosteric mechanism. We recently introduced a magnetic resonance-based protocol that allowed us to determine the coupling of intra- and interdomain structural sampling in apo Pin1. Here, we describe ligand-specific conformational changes that occur upon binding of pCDC25c and FFpSPR. pCDC25c binding doubles the population of the extended states compared to the virtually identical populations of the apo and FFpSPR-bound forms. pCDC25c binding to the WW domain triggers conformational changes to propagate via the interdomain interface to the catalytic site, while FFpSPR binding displaces a helix in the PPIase that leads to repositioning of the PPIase catalytic loop. Born et al. describe interdomain allostery in the two domain peptidyl-prolyl isomerase Pin1 upon binding of two ligands. These ligands couple population shifts of extended and compact states to changes in the catalytic site of Pin1.